Opuntia spinosisima Prickly Pear Cactus - Edward Gilman (EDIS, 2007)
The publication provides a comprehensive overview of Opuntia spinosissima, commonly known as the Prickly Pear Cactus. This native species, which is at risk of extinction in Florida, forms irregular clumps or shrub-like mounds in sandy soils and has a coarse texture. The plant’s modified stems, often mistaken for leaves, are covered with long spines and smaller glochids that can cause irritation. It thrives in full sun and well-drained soils, demonstrating high tolerance to drought, heat, and salt. The cactus produces bright red, cup-shaped flowers and edible fruits that mature in mid to late summer. The publication also discusses the plant’s uses in landscaping, its propagation methods, and its resistance to pests and diseases. Original publication date October 1999.